The Sacco-Vanzetti Affair : America on trial - Temkin, Moshik, 1971- (New Haven : Yale University Press, 2009)
What began as the obscure local case of two Italian immigrant anarchists accused of robbery and murder flared into an unprecedented political and legal scandal as the perception grew that their conviction was a judicial travesty and their execution a political murder. This book is the first to reveal the full national and international scope of the Sacco-Vanzetti affair, uncovering how and why the two men became the center of a global cause célèbre that shook public opinion and transformed America's relationship with the world. Drawing on extensive research on two continents, and written with verve, this book connects the Sacco-Vanzetti affair to the most polarizing political and social concerns of its era. Moshik Temkin contends that the worldwide attention to the case was generated not only by the conviction that innocent men had been condemned for their radical politics and ethnic origins but also as part of a reaction to U.S. global supremacy and isolationism after World War I. The author further argues that the international protest, which helped make Sacco and Vanzetti famous men, ultimately provoked their executions. The book concludes by investigating the affair's enduring repercussions and what they reveal about global political action, terrorism, jingoism, xenophobia, and the politics of our own time.
The two most famous prisoners in the world : from case to affair -- Americans divided : foreign interference and the execution of Sacco and Vanzetti -- This frightful America whose heart is made of stone : the transatlantic affair -- The mob of broadcloth-coated, heavy-jowled gentlemen : the Lowell Commission and the aftermath of the affair -- A kind of madness : the return of Sacco and Vanzetti -- Postscript : the place of Sacco and Vanzetti.
Includes bibliographical references (pages 225-304) and index.
Print version record.
In English.
JSTOR
Keywords: Sacco-Vanzetti Trial, Dedham, Mass., 1921.; Trials (Murder) -- Massachusetts -- Dedham; Affaire Sacco et Vanzetti, Dedham, Mass., 1921.; Procès (Meurtre) -- Massachusetts -- Dedham; LAW -- Criminal Law -- General; HISTORY -- United States -- 20th Century; Trials (Murder); Massachusetts -- Dedham; Sacco-Vanzetti-Fall; Sacco et Vanzetti, Affaire (1920-1927); Assassinat -- Procès -- Massachusetts (États-Unis); Sacco-Vanzettiaffären, Förenta staterna, 1921.; Rättsfall -- Förenta staterna -- 1920-talet.; Anarkister; 1921; dissertations; Academic theses; Academic theses; Thèses et écrits académiques.